A 28/38 GHz tuned reconfigurable antenna for 5G mobile communications - Samar A. Refaat; Hesham A. Mohamed; Abdelhady M. Abdelhady; Ashraf S. Mohra (Institute of Advanced Engineering and Science, 2023)
In this paper, a compact tuned reconfigurable microstrip antenna for fifth generation (5G) mobile communications is designed to operate at 28 GHz or 38 GHz or both frequencies. The proposed antenna can be reconfigured by using a group of PIN diodes switches across a slit in the upper traditional patch antenna or through the ground plane side. The tuning between the 28 GHz and 38GHz frequency bands can be achieved through ON/OFF states of the PIN diodes switches. The tuned reconfigurable antenna is simulated using CST software package and then fabricated and measured. The simulated and measured results show good agreement with a little deviation. The proposed tuned antenna is small in size with 18×11.25 mm2 overall area.